2020
DOI: 10.1055/s-0040-1716842
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Emergency Postpartum Hospital Visits in the Fourth Trimester

Abstract: Objective The concept of the “fourth trimester” emphasizes the importance of individualized postpartum follow-up. Women seek care for urgent issues during this critical time period. Our objective was to evaluate trends in presenting complaints and admissions in an emergency setting over the first 42 days following delivery. Study Design Postpartum hospital encounters within 42 days of delivery at our institution from 2015 to 2019 were studied. Demographic information, delivery route, and emergent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Infection is a leading cause of mortality and severe morbidity in the postpartum period, 1 and is one of the most common causes of a postpartum readmission or emergency department (ED) visit. [2][3][4][5][6][7][8] Readmissions and emergency department visits are most likely to occur during the first weeks after birth, with the largest proportion occurring within the first several days after discharge from the birth hospitalization. [2][3][4][5][6][7][8] Prevention of unscheduled hospital encounters, and the associated mortality and severe morbidity, during this early postpartum period is an opportunity to improve health outcomes for postpartum individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection is a leading cause of mortality and severe morbidity in the postpartum period, 1 and is one of the most common causes of a postpartum readmission or emergency department (ED) visit. [2][3][4][5][6][7][8] Readmissions and emergency department visits are most likely to occur during the first weeks after birth, with the largest proportion occurring within the first several days after discharge from the birth hospitalization. [2][3][4][5][6][7][8] Prevention of unscheduled hospital encounters, and the associated mortality and severe morbidity, during this early postpartum period is an opportunity to improve health outcomes for postpartum individuals.…”
Section: Introductionmentioning
confidence: 99%
“…These infections include wound infections, major puerperal infections, urinary system infections, inflammatory diseases of reproductive organs, and amniotic cavity infections. Additionally, the risk of a postpartum hospital encounter is further influenced by other conditions and procedures during the birth hospitalization, such as mode of birth, 6,[8][9][10][11] body mass index (BMI), 5,6,12,13 hemorrhage, 14,15 and severe obstetrical morbidity. 4,11,16 The ability to identify which genitourinary and wound infection patients are most at risk of an unscheduled postpartum hospital encounter is needed to inform prevention efforts.…”
mentioning
confidence: 99%
“…1,2 In a retrospective study, researchers noted that 491 of 8589 births (5.7%) resulted in at least 1 presentation to the hospital within the first 42 days postpartum with 75.5% occurring during the first 3 weeks after childbirth. 14 An associated risk factor for seeking postpartum hospital care included cesarean delivery surgery. 14 In 2013, the World Health Organization declared postnatal health and well-being support of women and newborns as a global priority.…”
Section: Introductionmentioning
confidence: 99%
“…14 An associated risk factor for seeking postpartum hospital care included cesarean delivery surgery. 14 In 2013, the World Health Organization declared postnatal health and well-being support of women and newborns as a global priority. 15 Bingham et al 16 suggested priority strategies to decrease maternal mortality and morbidity in the first year following childbirth including (1) standardizing hospital discharge postpartum education; (2) increasing awareness of potential complications; and (3) enhancing social and mental health support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation